Validasi Kit Enzyme-Linked Immunosorbent Assay Komersial untuk Analisis Hormon Estradiol dan Progesteron Darah Kambing Kacang (VALIDATION OF COMMERCIAL ENZYME-LINKED IMMUNOSORBENT ASSAYKIT FORANALYSIS OF ESTRADIOLANDPROGESTERONE HORMONE IN BLOOD OF KACANG - Setiadi, Dedi Rahmat; Supriatna, Iman; Agil, Muhammad (Jurnal Veteriner; Vol 15 No 4 (2014), 2015)
The aim of this study was to evaluate the capability of two human commercial enzyme-linkedimmunosorbent assay (ELISA) kits(DRG International Inc.,Germany and GBC Taiwan) for measuringestradiol (E2) and progesterone (P4) in plasma of kacang goat. Three healthy and non pregnant femalekacang goats aged 2-3 years with regular estrous cycles were used in this study. Blood samples werecollected from the jugular vein using a 21G venoject every two days and it was intensified every day duringthe period before heat. Collected plasma were stored at -20ºC until the analysis. Capability validationwas conducted by measuring accuracy (parallelism test), sensitivity and precision.Parallelism test usingDRG commercial kit showed that sample curvewas parallel with standard curve of E2 and P4. In contrastit was not parallel with standard curve of GBC commercial kit. Sensitivity was measured from the lowesthormones concentration of E2 and P4 at 90% binding that were 25 pg/ml and 0.14ng/mL in DRG kit, whilein GBC kit were 5 pg/mL of E2 and 0.2 ng/mL of P4, respectively. Coefisien of variation of intra- andinterassay for both ELISA commercial kits were less than10%. It can be concluded that DRG commercialELISA kit E2 and P4 can be used to analyse female kacang goat blood plasma, while GBC commercialELISA kit E2 and P4 are not recommended.
Keywords: kacang goat, estradiol, progesteron, ELISA